Thermal characteristics and thermal stress analysis of a superheated water/steam solar cavity receiver under non-uniform concentrated solar irradiation. (25th January 2021) - Fang, Jiabin; Zhang, Canghong; Tu, Nan; Wei, Jinjia; Wan, Zhenjie
Highlights: The thermal characteristics and thermal stress were calculated for a cavity receiver. The three-dimensional temperature and thermal stress distributions were obtained. The causes of thermal stress induced by different temperature gradients were analyzed. The features of thermal stress on the membrane wall were also emphasized. Abstract: Solar cavity receiver is a vital component in a solar power tower (SPT) system, where concentrated solar irradiation is absorbed, converted into heat and carried away by a kind of heat transfer fluid. The cavity receiver usually suffers from the high-flux and non-uniform concentrated solar irradiation, which would cause local overheating, large temperature gradient and even thermal stress fracture of the receiver and bring challenges for the safety of its daily operation. Therefore, it is necessary to investigate the thermal and mechanical performance of the solar cavity receiver. In the present study, a superheated water/steam solar cavity receiver with three boiling panels and a superheater was chosen as the physical model. An integrated simulation method, which couples the Monte-Carlo ray tracing (MCRT) method, the appropriate heat transfer correlations, the finite volume method (FVM) and the finite element method (FEM), was employed to simulate the complicated heat transfer process inside the receiver and conduct the thermal stress analysis for the absorber panels. With this method, the three-dimensional wall temperature and thermal stress distributions were gained both on the boiling panels and the superheater, and the causes of thermal stress induced by different temperature gradients were analyzed in detail. The following results were obtained: 1) The heat flux, wall temperature and equivalent thermal stress distributions all appear highly non-uniform on the absorber panels; 2) The hot spots can be found on the membrane wall between the elbows of the boiling panels, which can easily generate the high thermal stress due to the large temperature gradient with their surroundings; 3) The bi-axial stress at the outer and inner radius of the boiling tubes can be created by the large radial temperature gradient, and the thermal stress varies as a cosine distribution across the circumference of the superheated tubes, which is induced by the large temperature gradient in the circumferential direction. Besides, the spot-like areas with high thermal stress can also be found on the superheated tubes due to the considerable nonlinear axial temperature gradient. Moreover, the thermal stress on the membrane wall connected with both the boiling and the superheated tubes has the definite directionality, which shows parallel to the tubes or perpendicular to the tubes; 4) The thermal stress concentration always occurs at the high-temperature and structural discontinuity locations. Here, the thermal stress of the superheater is 360 MPa higher than that of the boiling panels. In general, the superheater has both the higher wall temperature and thermal stress, which is more crucial for the safe operation of the superheated water/steam solar cavity receiver.